Endocrine disruptors - Moguilevsky, Jaime A. (2006)
An endocrine disruptor (ED) is a synthetic chemical that when absorbed into the body either mimics or blocks hormones and disrupts the body's normal functions. This disruption can happen through altering normal hormone levels, halting or stimulating the production of hormones, or changing the way hormones travel through the body, thus affecting the functions that these hormones control. Chemicals known to be human ED include diethylstilbestrol (DES), dioxin, PCBs, DDT, and other pesticides. Many chemicals, particularly cosmetics (UV filters) and plasticizers, are suspected to be endocrine disruptors based on experimental studies in animals.